2013
DOI: 10.1152/physiolgenomics.00096.2013
|View full text |Cite
|
Sign up to set email alerts
|

Feeding soy protein isolate and treatment with estradiol have different effects on mammary gland morphology and gene expression in weanling male and female rats

Abstract: Ronis MJJ. Feeding soy protein isolate and treatment with estradiol have different effects on mammary gland morphology and gene expression in weanling male and female rats. Physiol Genomics 45: 1072-1083. First published September 17, 2013 doi:10.1152/physiolgenomics.00096.2013.-Isoflavones are phytochemical components of soy diets that bind weakly to estrogen receptors (ERs). To study potential estrogen-like actions of soy in the mammary gland during early development, we fed weanling male and female Sprague… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 61 publications
4
13
0
Order By: Relevance
“…al. 2009, Ronis et al, 2011a) or in estrogen-sensitive reproductive tissues such as the mammary, uterus or testis (Ronis et al, 2012; Miousse et al, 2013; Ronis et al, 2014; Ronis et al, 2016). These data suggest that although studies on the effects of pure isoflavones on CYP expression and activity may be of importance in consumers of isoflavone supplements, they probably have limited relevance to soy consumers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. 2009, Ronis et al, 2011a) or in estrogen-sensitive reproductive tissues such as the mammary, uterus or testis (Ronis et al, 2012; Miousse et al, 2013; Ronis et al, 2014; Ronis et al, 2016). These data suggest that although studies on the effects of pure isoflavones on CYP expression and activity may be of importance in consumers of isoflavone supplements, they probably have limited relevance to soy consumers.…”
Section: Discussionmentioning
confidence: 99%
“…In studies in cultured pig granulosa cells genistein was reported to inhibit CYP11A1 activity (cholesterol side chain cleavage enzyme) which catalyzes the conversion of cholesterol to pregnanolone and reduced progesterone production (Piasecka-Srader et al 2014). Interestingly in this regard, Miousee et al (2013) reported that feeding SPI compared to casein diets reduced serum progesterone in weanling female but not male rats. In contrast, the reported effects of genistein on CYP19 (aromatase) expression and activity are inconsistent.…”
Section: Effects Of Soy and Isoflavones On Cyp-dependent Steroid Metamentioning
confidence: 99%
“…1,2 Moreover, we have observed dramatically different gene expression profiles in liver, bone, mammary gland, and uterus of adult and pre-pubertal rats after feeding SPI relative to those elicited by 17β estradiol (E2). 2125 These data suggest that the endocrine effects of purified isoflavones relative to feeding SPI are quite different. The current study was designed to determine if feeding SPI, the sole protein source in soy infant formula to pre-pubertal male rats has different effects than estrogens on male reproductive development during a developmental window corresponding to human neonatal and early childhood development.…”
Section: Introductionmentioning
confidence: 93%
“…The most intensively studied nutraceutical flavonoids are the soy derived isoflavones genistein and daidzein, and the daidzein metabolite equol. Unlike other flavonoids, the isoflavones in their purified form have been shown to possess estrogenic properties in vitro and in animal models, including the ability to produce uterine hypertrophy or reproductive tract malformations, reduce testis size, inhibit androgen production, reduce fertility, and stimulate estrogen-dependent tumor growth (36,37,45,48,49,51,52,56). Since evidence emerged demonstrating health risks following hormone replacement therapy in post-menopausal women, menopausal women have increasingly turned to use of dietary supplements to treat symptoms such as hot flashes, depression and bone loss.…”
Section: Nutraceuticalsmentioning
confidence: 99%